Depressive Symptoms in Emerging Adults with Early Left-Behind Experiences in Rural China. Issue 4 (19th May 2019) - Lan, Xiaoyu; Wang, Wenchao; Radin, Rendy
Abstract: The current study aimed to compare depressive symptoms in emerging adults with early left-behind experiences (LB-A) and their counterparts (non-LB-A) in China. Of importance, guided by a risk and resilience ecological framework, we examined the potential interactive roles of peer support, parent support, and personal characteristics (i.e., grit) on depressive symptoms. A total of 458 LB-A and 1, 656 non-LB-A participants were involved in the study. The findings showed that the LB-A group perceived higher levels of depressive symptoms than the non-LB-A group. Moreover, in the context of higher levels of peer support, grit was found to buffer depressive symptoms for the LB-A group.